TEACHER’S ASSESSMENT PROCESS: Teacher’s Assessment Process - Qamar, Khadija (Pakistan Armed Forces Medical Journal, 2015)
EDITORIALThe reflective nature of the life long process of Teacher’s assessment refers to a systematic exploration of all characters of a teacher’s performance1. Teacher quality assessment commonly includes reviews of qualifications, tests of the teacher’s knowledge, observations of practice, and measurements of the student learning gains. Evaluations of teacher quality are currently used for employment and contract decisions2. It recognizes the strengths and weaknesses, encourages professional development and provides a process for both formative and summative assessment; based on either internal or external assessing bodies. Type of teaching certification, advanced degrees or certifications are important components of professional growth ongoing regular formative assessments of performance are available for the sole purpose of nurturing professional growth and improved training, and summative evaluations of teacher performance for the purpose of favorable sustained occupation. This in turn prompts individuals to rethink, go in new directions, and change previously applied strategies.  This not only provides the awareness so that a teacher can develop different approaches for the developmentof teaching skills and professional behaviors, but also enables reflection of clear learning goals and scales in order to measure these goals, the measurement in turn helping in the assessment of the student’s progress. Moreover, it helps in identifying critical information when it comes to assessing academic examining errors in reasoning, practicing skills, strategies, and processes of the teacher’s ability andin improving the quality of education and the academic environment of the institute3. While standards for teaching practice and student learning are vital, each teacher should also define student learning objectives to be assessed. A teacher’s input can provide vital learning objectives for the contextualized environments of each learning environment. As said earlier, it is important to embrace extra ordinary prospects of all teachers from the start of their teaching careers. It is improbable to expect from even end owed learned teachers to meet the same expectations as more practiced educators. Expectations should increase progressively during coaching years in the establishments.Sources of InformationPotential sources of evidence on effectiveness of teaching are peer observations, peer review of course material, external expert ratings, self-rating, employer rating ,teaching scholarships, teaching rewards, learning outcome measures and instruction course portfolios5. These sources can help to draw evidence from one or more source and can leverage the strengths of each source to the weaknesses of the other source. There has been a recent trend toward augmenting ratings with other data sources to broaden and deepen evidence bases.Evaluation systems should use multiple sources to determine whether teachers have met performance expectations as no single measurement can provide a complete depiction of a teacher’s performance. The 360 degrees multisource feedback (MSF) model, recommended by the experts, best fits to evaluate teaching performance by measuring different aspects of teaching effectiveness6.Formative decisionsSelf-assessmentSelf-assessment focuses on understanding the teacher’s motivations and attitudes towards improvement. The value system of the teacher plays an important role in improvement, and self-assessment can be done to improve and shape teaching at a particular time of the teaching. This should neither involve threat of punishment nor the promise of reward. Student data can be obtained from portfolios and student interviews to provide teachers with feedback about their practice, and appoint teachers in learning practices that are free from employment-based decisions. Some newly introduced evaluation systems entail that teachers conduct a self-assessment analysis, establish professional growth aims, and take part in a study group with contemporaries to follow a topic of shared concern7.Summative decisionsCriteria for summative evaluations should be developed in cooperation with the administrators and teachers while adhering to strict guidelines, forms, and timelines. Letter of recommendation by the dean based on his or her personal expert advice can help the faculty committee to formulate decisions regarding the promotion and progression of a teacher. The dean uses evidence of the teacher’s effectiveness from research publications and clinical practice since he is the person who has access to all the teacher activities through documents and direct observations8. Different data can be obtained through studentratings, teaching scholarships, administrative data, and mentor review for the summative decisions.Program decisionProgram evaluation standards can be used to evaluate the process of curriculum admissions, graduation requirements and program effectiveness. These decisions are based on the consultation from the documents to satisfy the accreditation bodies. Data through student ratings, exit and alumnirating and employers rating can help making program decisions9. Teachers are involved in all the academic activities with the students such as teaching and curriculum development, and any change in the above mentioned sources can provide feedback regarding the effectiveness of the teacher.Steps to Establish The Integrity of Teacher AssessmentThe 360 degrees multisource feedback (MSF) model is a best criterion to evaluate teaching performance, as it utilizes all the available data from all the above mentioned sources. Moreover, it can provide more accurate and equitable decisions than the one based on just a single source. Process of evaluation should start with student ratings and reviewing other sources of evidence.  One has to choose the best combination of sources for the faculty and map out a plan, one at a time, for a more precise assessment of the decision followed with integrity, validity and reliability of the evidence provided. Rating scales should include at least two levels at or above standards and two levels below standards, and there should be no doubt about the desired levels that meet the standards. Teachers deserve clear information about whether they are meeting the overall expectations. Teachers who fail to meet the conventional standards should be offered professional growth, remediation procedures, and prospects to observe their peers. They should also be given sufficient time, support, and assistance towards meeting the standards. Experts of validity provide evidence on the psychometric standards which is that the global items account for most of the variance in several criterion measures of teaching effectiveness10. Student feedback on evaluations of teaching, despite many flaws, is widely used as a primary and frequently convenient tool to measure teaching effectiveness. There are numerous characteristics of teaching which cannot be evaluated by the students, as students generally lack know-how on the standard scales and about the ability to judge the level of knowledge of the teacher, content expertise, teaching methods, course materials, assessment instruments and grading practices. Therefore, they provide little portion of the information regarding teaching effectiveness. Developers of evaluation instruments and systems progressively identify the wisdom and benefits of designing evaluation processes that intentionally foster and support teacher growth11.A teacher’s continuous commitment to learning, skill achievement, and improvement to practice is essential for meeting the student’s learning needs. Assessment and evaluation are crucial for determining whether teachers are, in fact, gaining the content, skills, and characters necessary to meet institute standards for student learning. Assessment and evaluation are also indispensable for identifying any supplementary professional learning that a teacher may require. Intellectuals label teacher evaluation as a managerial issue that include improving teaching climate, having the head of institute become an instructional leader, and constructing bridge between institute improvement, professional development, teacher evaluation and student learning12.